ELASTIC NONLINEAR DYNAMICS OF MOTION OF SLIDE OF VERTICAL TURNING MACHINE FOR WORKING OF SOLID-ROLLED RAILWAY WHEELS - Pogrebnyak, R. P. (Science and Transport Progress, 2017)
Purpose. The article is aimed to determine the conditions of a dynamic error formation of contour machine cutting of surface of the real railway wheel flange by the cup-tip tool and propose the ways of reducing the errors. Methodology. The problem was solved by the creation of dynamic nonlinear and elastic calculation model with further modeling of its loading by the external force factors. The values of forces were obtained by analytical and experimental methods. The calculation scheme of the equilibrium support is a nonlinear two-mass system, a dynamic model of slide - single-mass with one degree of freedom. The basis of the mathematical description of technological loads is the results of factory experiments, as well as analytical generalizations obtained as a result of the comparison of several schemes of the formation of the wheel flange. Analytical determination of the components of the cutting force takes into account the changes in the kinematic parameters of the cutting mode when the profiling is done using a shaped tool. Findings. During processing of the wheel flange the radial and axial components of the cutting forces that load slide and slide-block of machine are alternating. There are conditions in drive of slide and slide-block when the gaps appear, and it is possible at any profile geometry of the wheel. The peculiarities of loading of the slide and slide-block forming a flange (with biharmonic allowance) cause the occurrence of the processing areas where the gaps increase many times in drives of mechanical transmissions and error of forms increases. The dynamic system of the drive is quite tough and high-frequency and it is sensitive to the presence of gaps. Originality. The author created elastic nonlinear dynamic models of support and slide. In accordance with the model it is written and solved equations of motion of the masses and loading of the connections. The conditions of the stable motion were found. Practical value. It is determined by modeling the qualitative and quantitative terms of stable motion without gaps. It is recommended to change the weight of counterweight.